Bioversity for food and nutrition: promoting food security and nutrition through institutional markets in Brazil - Beltrame, Daniela; Borelli, Teresa; Oliveira, Camila; Coradin, Lídio; Hunter, Danny (Food and Agriculture Organization of the United Nations, 2021)
A well-established political and regulatory framework exists in Brazil to promote food security and nutrition. Among its key elements are the Food Purchase Programme (PAA) and the National School Feeding Programme (PNAE), two institutional food procurement programmes that provide equitable support to family farmers by acquiring their products at a fair price and directing them to public schools, public programmes and social organizations. Both PNAE and PAA were identified by the Biodiversity for Food and Nutrition Project (BFN) (which is funded by the Global Environment Facility) as potential entry points to improve nutrition and livelihoods by linking them to native biodiversity and its conservation. BFN increased awareness on the importance and nutritional value of food species from Brazilian biodiversity through advocacy and capacity building workshops and by engaging in strategic alliances and partnerships with key actors involved in PNAE, PAA and related policies.